Edukasi Dampak Negatif Pernikahan Dini Terhadap Peningkatan Kesehatan Reproduksi Remaja Siswa SMP Negeri Model Terpadu Madani Palu - Sari, Waode Fitrah; Arniawan, Arniawan; Lestari, Katrina Feby; Sabir, Sabir (Abdimas Indonesian Journal, 2025)
Early marriage has significant impacts on the reproductive health system, especially in adolescent females. The immaturity of reproductive organs and physical development increases the risk of adverse outcomes. Adolescents' reproductive organ immaturity and incomplete physical development increase risks of premature birth, infant disability, Low Birth Weight, infection, and anemia during pregnancy, which can potentially cause abortion, higher mortality, and hemorrhage risks due to underdeveloped uterine muscles. The purpose of this community service program aimed to educate junior high school students about the negative impact of early marriage on adolescent reproductive health The program employed socialization sessions, interactive discussions and evaluation. Evaluation was used to assess the level of knowledge through pre-test and post-test questionnaires. Among 36 respondents, the pre-test results showed that the level of knowledge about the negative impact of early marriage on adolescent reproductive health was: 19 people (53%) in the poor category, 10 people (28%) in the moderate category, and 7 people (19%) in the good category. In the post-test results, 4 people (11%) were in the poor category, 3 people (8%) in the moderate category, and 29 people (81%) in the good category. The comparative results demonstrate an improvement in knowledge and understanding among junior high school students regarding the presented material. This activity was successfully conducted through effective collaboration.